The Effect of Vacuum Annealing of Magnetite and Zero-Valent Iron Nanoparticles on the Removal of Aqueous Uranium - R. A. Crane; T. B. Scott (Journal of Nanotechnology)
As-formed and vacuum annealed zero-valent iron nanoparticles (nano-Fe0) and magnetite nanoparticles (nano-Fe3O4) were tested for the removal of uranium from carbonate-rich mine water. Nanoparticles were introduced to batch systems containing the mine water under oxygen conditions representative of near-surface waters, with a uranyl solution studied as a simple comparator system. Despite the vacuum annealed nano-Fe0 having a 64.6% lower surface area than the standard nano-Fe0, similar U removal (>98%) was recorded during the initial stages of reaction with the mine water. In contrast, ≤15% U removal was recorded for the mine water treated with both as-formed and vacuum annealed nano-Fe3O4. Over extended reaction periods (>1 week), appreciable U rerelease was recorded for the mine water solutions treated using nano-Fe0, whilst the vacuum annealed material maintained U at <50 μg L−1 until 4 weeks reaction. XPS analysis of reacted nanoparticulate solids confirmed the partial chemical reduction of UVI to UIV in both nano-Fe0 water treatment systems, but with a greater amount of UIV detected on the vacuum annealed particles. Results suggest that vacuum annealing can enhance the aqueous reactivity of nano-Fe0 and, for waters of complex chemistry, can improve the longevity of aqueous U removal.